Essential oil composition of Achillea teretifolia from Turkey - Aslan, S.; Evren, H.; Konuklugil, B.; Turkoglu, I.; Kartal, M. (Springer, 2009)
[Abstract Not Available]
Keywords: Antimicrobial Activities